E-Commerce Developments and Strategies for Value Creation: The Case of Russia And China - STARTSEVA, ELENA; XIA, ZHANG HONG; RATHNAYAKE, DILESHA NAWADALI (The journal of contemporary issues in business and government, 2021)
E-Commerce has a significant impact on the economy and business productivity and currently has a chance to become widespread due to its simple applications. This provides an opportunity to "cross borders" as new entrants, business models, and technology changes break down barriers that previously separated one industry from another. This increases competition and innovation, which is likely to increase overall economic efficiency. In recent years, China has played an increasing role in E-Commerce, both domestic and international transactions. In these circumstances, the country's leadership faced an obvious need to form comprehensive domestic legislation in E-Commerce and ensure compliance with international norms and standards.